2019
DOI: 10.1111/jgs.15850
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Patients in Identifying Their Values‐Based Health Priorities

Abstract: OBJECTIVES Patient Health Priorities Identification (PHPI) is a values‐based process in which trained facilitators assist older adults with multiple chronic conditions identify their health priorities. The purpose of this study was to evaluate patients’ perceptions of PHPI. DESIGN Qualitative study using thematic analysis. SETTING In‐depth semistructured telephone and in‐person interviews. PARTICIPANTS Twenty‐two older adults who participated in the PHPI process. MEASUREMENTS Open‐ended questions about patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 22 publications
(52 reference statements)
0
40
0
Order By: Relevance
“…They also reported that initial fear among physicians that patients would formulate unrealistic goals was unjustified; if patient were guided through the SDM process, they formulated personal and realistic goals. This was confirmed by the study of Feder (2019) who also found that discussing personal goals led to a better relationship with physicians [76].…”
Section: Discussionmentioning
confidence: 67%
“…They also reported that initial fear among physicians that patients would formulate unrealistic goals was unjustified; if patient were guided through the SDM process, they formulated personal and realistic goals. This was confirmed by the study of Feder (2019) who also found that discussing personal goals led to a better relationship with physicians [76].…”
Section: Discussionmentioning
confidence: 67%
“…Table 1 incorporates the characteristics and quality appraisal of the included studies. There were n = 764 participants (age range: 65-100 years, M: 78 years; 64% female) included in the 15 studies, three mixed methods studies (Melville et al, 2002;Rose et al, 2019;Saajanaho et al, 2016) and 12 qualitative studies (Brown et al, 2014;Coylewright et al, 2016;Efraimsson et al, 2006;Feder et al, 2019;Gorawara-Bhat et al, 2008;Hjelle et al, 2016;Huang et al, 2005;Kuluski et al, 2013;Pikkarainen et al, 2018;Schellinger et al, 2018;Schulman-Green et al, 2006;van Seben et al, 2019). Most studies chose purposive sampling.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies chose purposive sampling. Data collection was via interviews (Brown et al, 2014;Efraimsson et al, 2006;Feder et al, 2019;Gorawara-Bhat et al, 2008;Hjelle et al, 2016;Huang et al, 2005;Kuluski et al, 2013;van Seben et al, 2019), questionnaires (Saajanaho et al, 2016;Schulman-Green et al, 2006), or a combination of both (Coylewright et al, 2016;Melville et al, 2002;Rose et al, 2019). Pikkarainen et al (2018) used nonparticipant observation, and Schellinger et al (2018) analyzed the data from electronic medical records that had documented direct patient quotes or patient validated statements.…”
Section: Resultsmentioning
confidence: 99%
“…This study opens 3 new avenues for further investigation. By identifying PPC notes, we can longitudinally assess care for patients throughout VA facilities and understand changes in health care delivered after PPC encounters [ 6 , 21 ]. We can identify patterns and consistency in how social workers and other clinicians document patient priorities over the course of multiple interactions with patients [ 3 ].…”
Section: Discussionmentioning
confidence: 99%